Embracing Full Openness: Transitioning ESNBU from CC BY-NC to CC BY - Stanislav Bogdanov (English Studies at NBU)
This editorial explores the rationale behind transitioning the ESNBU journal's content licensing from CC BY-NC (Attribution-NonCommercial) to CC BY (Attribution). For a decade, the journal operated under the CC BY-NC license to restrict commercial use, but this approach has unintentionally limited its reach and visibility. The objective is to address these limitations and promote unrestricted dissemination of scholarly content. The analysis involved a review of the journal's indexing history, feedback from database providers, and usage statistics over the past ten years. We examined cases where the NC clause hindered the journal's inclusion in databases, especially those operated by commercial or for-profit entities. We also reviewed existing literature on licensing impacts in open access publishing to understand broader trends and potential benefits of a transition to CC BY. The study found that the NonCommercial restriction created significant barriers to the journal's visibility and dissemination. Several commercial and academic databases opted not to index the journal's content due to ambiguity around the "commercial use" clause. By transitioning to a CC BY license, we anticipate enhanced indexing opportunities, increased content integration into educational resources, and a broader reach, ultimately leading to higher citation rates and greater impact. Moving to a CC BY license aligns the journal with the principles of Open Science, fostering unrestricted access to knowledge. This change supports wider dissemination, potential for increased collaboration, and enhanced visibility in academic databases. Future analysis will focus on measuring the impact of this transition on the journal's citation metrics, user engagement, and overall accessibility.